2008
DOI: 10.1080/14756360802051230
|View full text |Cite
|
Sign up to set email alerts
|

Quinic acid derivatives from Saussurea triangulata attenuates glutamate-induced neurotoxicity in primary cultured rat cortical cells

Abstract: The leaves of Saussurea triangulata (Compositae) have been eaten with rice as a wrapping vegetable for preventing neuroaging. However, the components responsible for the neuroprotective effects of S. triangulata still remain unidentified. In the process of investigating the neuroprotective activity of S. triangulata, we found that a methanol extract of S. triangulata exhibited significant protection against glutamate-induced toxicity in primary cultured rat cortical cells. Three quinic acid derivatives were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The bioassay-guided isolation led to the identification of 5-CQA methyl ester (10) from the n-BuOH fraction of Saussurea triangulata (Compositae). 108 Compound 10 exhibited potent neuroprotective effects against glutamateinduced primary cultured rat cortical cell toxicity at 1 μM (46.2 ± 1.5% cell viability). ceae), a plant used as Chinese folk medicine, were shown to prevent glutamate-induced primary cultures of rat cerebral cortical neuron death by restraining the increase of Ca 2+ and the production of reactive oxygen species (ROS) (concentration range of 0.1−5 μM).…”
Section: Biological Activities Of Natural Cqasmentioning
confidence: 95%
See 3 more Smart Citations
“…The bioassay-guided isolation led to the identification of 5-CQA methyl ester (10) from the n-BuOH fraction of Saussurea triangulata (Compositae). 108 Compound 10 exhibited potent neuroprotective effects against glutamateinduced primary cultured rat cortical cell toxicity at 1 μM (46.2 ± 1.5% cell viability). ceae), a plant used as Chinese folk medicine, were shown to prevent glutamate-induced primary cultures of rat cerebral cortical neuron death by restraining the increase of Ca 2+ and the production of reactive oxygen species (ROS) (concentration range of 0.1−5 μM).…”
Section: Biological Activities Of Natural Cqasmentioning
confidence: 95%
“…In another report, three new 4,5-DCQA derivatives (92−94), featuring different moieties at C-1, together with five known CQA derivatives were identified. 82 Their free radical scavenging activities were performed by DPPH, ABTS, and ferric reducing antioxidant power (FRAP) assays, and the abilities of these compounds increased in the order 5-CQA (9) < DCQA derivatives (91−94) < DCQAs (71 and 75) < TCQA (108). These results suggested that the antioxidant ability of CQAs was associated with the number of caffeoyl groups.…”
Section: Monocaffeoylquinic Acids (Mcqas)mentioning
confidence: 95%
See 2 more Smart Citations
“…Three isomers were detected at m/z 557 and they were assigned as methyl diferuloylquinates (18)(19)(20). From the previous discussion of methyl quinates, it is generalized that the most hydrophilic isomer is methyl 3,4-diferuloylquinate 18 which produced the MS 2 (Fig.…”
Section: Characterization Of Methyl Diferuloylquinates (M R 557)mentioning
confidence: 98%